Transforming Food Systems Under Climate Change through Innovation - Campbell, Bruce M.; Thornton, Philip K.; Loboguerrero Rodriguez, Ana María; Dinesh, Dhanush; Nowak, Andreea C. (Cambridge University Press, 2023)
Our food systems have performed well in the past, but they are failing us in the face of climate change and other challenges. This book tells the story of why food system transformation is needed, how it can be achieved and how research can be a catalyst for change. Written by a global interdisciplinary team of researchers, it brings together perspectives from multiple areas including climate, environment, agriculture, and the social sciences to describe how different tools and approaches can be used to tackle food system transformation. It provides practical, actionable insights for policymakers and advisors, demonstrating how science together with strong partnerships can enable real transformation on the ground. It also contributes to the academic debate on the transformation of food systems, and so will be an invaluable reference for researchers and students alike.